2022
DOI: 10.1101/2022.08.24.505183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of bacterial recombination in the human gut microbiome

Abstract: Horizontal gene transfer is a ubiquitous force in microbial evolution. Previous studies have shown that the human gut is a hot spot for gene transfer between species, but the more subtle exchange of variation within species — collectively known as recombination — remains poorly characterized in this ecosystem. Here, we show that the genetic structure of the human gut microbiome provides unique opportunities to measure individual recombination events directly, enabling quantitative comparisons of recombination … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 124 publications
(199 reference statements)
0
15
1
Order By: Relevance
“…9; Appendix H). Previous estimates of LD in this species have suggested that E. rectale strains in different hosts experience high rates of homologous recombination (Good, 2022; Liu and Good, 2024), which provides a natural opportunity for exploring the homoplasy metrics discussed above. The core genomes of these strains contained a total of 338,669 synonymous single-nucleotide variants (SNVs), the vast majority of which were rare (median minor allele frequency of 0.6%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9; Appendix H). Previous estimates of LD in this species have suggested that E. rectale strains in different hosts experience high rates of homologous recombination (Good, 2022; Liu and Good, 2024), which provides a natural opportunity for exploring the homoplasy metrics discussed above. The core genomes of these strains contained a total of 338,669 synonymous single-nucleotide variants (SNVs), the vast majority of which were rare (median minor allele frequency of 0.6%).…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that at larger coordinate distances, the gene synteny of individual strains might start to differ from the E. rectale reference genome, which could make it harder to identify the precise distance between sites. To include pairs of sites with larger recombination rates, we recorded analogous haplotype counts between 10 3 pairs of randomly selected genes. These randomly sampled pair of genes are typically separated by hundreds of kilobases in the reference genome, which is longer than the typical recombination length in bacteria (Liu and Good, 2024). This suggests that their recombination rate should approach a constant value, R max = lim 𝓁→∞ R (𝓁).…”
Section: Case 1: Both Single Mutants Are Strongly Deleteriousmentioning
confidence: 99%
See 2 more Smart Citations
“…One important assumption of applying an SFS-based analysis is quasi-independence between sites, i.e., free recombination between sites (Bustamante et al 2001, Genetics). While bacteria reproduce asexually, most commensal gut bacteria experience extensive recombination (Vos and Didelot 2009, ISME; Liu and Good 2023, bioRxiv; Garud and Good et al 2019, PLoS Biology; Lin and Kussel 2019, Nature Methods; Smith et al 1993, PNAS). This recombination plays a critical role in shuffling genetic material and breaking up correlations between loci in the genome on long timescales exceeding within-host evolution.…”
Section: Introductionmentioning
confidence: 99%